Exploring Ecological Justice in the Regulatory Framework of Land Ownership, Utilization, Control, and Inventory in Indonesia - BASUKI, Agung; KARJOKO, Lego; HANDAYANI, I Gusti Ayu Ketut Rahmi (Journal of Environmental Management and Tourism; Vol 14 No 7 (2023): JEMT, Volume XIV, Issue 7(71), Winter 2023DO - 10.14505/jemt.v14.7(71).11, 2023)
The aim of this study is to provide a comprehensive analysis of environmental justice elements in land inventory, tenure, ownership, use and use (IP4T) management, as described in TAP MPR IX/2001 and Government Regulation No. 16. 2004 on land administration. This study uses a standard legal research method integrating both a legal and conceptual approach. The author's study indicates that environmental justice is included in the IP4T law, as stated in TAP MPR IX/2001, as well as in Government Law No. 16 on Spatial Planning. According to Article 23 of Government Regulation No. 16/2004, IP4T maps must be taken into account for all spatial and regional planning. These maps contain more than just information on land ownership, use, and use. In addition, the IP4T dataset includes assessments of land capacity and valuation, so environmental dimensions associated with land are examined. The definition of environmental justice can be derived from Section 3, Section 5 and Section 6, Paragraph (2) of TAP MPR IX/2001. However, in practice, many inconsistencies remain and undermine basic principles of environmental justice. These irregularities are particularly widespread in the context of the implementation of IP4T (Integration Policy for Transition) within the mining industry.